Development of River Tubing as a Special Interest Tourism in Kawinda To’i Tourism Village: A Youth Perspective - Feriyadin; Anisa; Kausar, Nova; Wahyudin, Muhammad Ade (Universitas Muhammadiyah Jember, 2024)
The development of interest-based river tubing enhances the destination’s appeal and positively impacts the local economy through active community participation in tourism management. This study aims to analyze the potential and opportunities for river tubing development, with a focus on the role of youth in tourism development and strategies to support their involvement in optimizing local tourism potential. Using a phenomenological qualitative approach with descriptive-analytical methods, data was collected through participatory observation, focus group discussions (FGD), and documentation. The research sample consists of 20 informants from tourism operators, nature enthusiast communities, Tourism Awareness Groups, youth organizations, local youth, Tambora National Park managers, and the Kawinda To’i village government. The findings indicate that the primary attraction of river tubing in Kawinda To’i Village, Tambora District, Bima Regency, lies in its surrounding natural beauty, including the route flanked by large rocks, dense trees, and a refreshing panorama. The relatively smooth and safe river flow, combined with easy accessibility, constitutes the main advantages supporting the existence of this tourist attraction. River tubing provides a refreshing adventure experience and plays a significant role in supporting local economic growth. Youth act as innovators and primary implementers in this activity, contributing through various forms of participation, including ideas, skills, effort, and resources. Strategic approaches to engage youth in river tubing management include interactive communication, cooperation among youth, communities, stakeholders, and village governments, training for self-reliance, and the provision of adequate facilities. Support from the government and relevant parties, along with the implementation of the principle of cooperation, empowers youth to act as driving forces in the sustainable management of tourism, maintaining ecosystem balance, and enhancing community welfare. Theoretically, this approach supports the concept of community-based tourism, emphasizing the vital role of youth as agents of change in the development of sustainable special-interest tourism, thereby enriching the literature on youth leadership in community-based tourism destination management